1993
DOI: 10.1002/chin.199316192
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: New Quinolones. Part 1. Synthesis of New Pyrido(3,2‐h)quinoline Derivatives and Their Antibacterial Activities.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…6-Chloro-1-(2-hydroxyethyl)-4-oxo-1,4-dihydro- [1,7]phenanthroline-3-carboxylicacid (1a) The parent molecule was prepared from 5-amino-8-chloro quinoline on reaction with diethyl ethoxymethelene malonate and cyclized in diethyl ether; further condensation with chloroethanol gave ester, which finally hydrolyzed to title compounds (Lee et al, 1992). 1 6-Hydroxy-1-(2-hydroxyethyl)-4-oxo-1,4-dihydro- [1,7]phenanthroline-3-carboxylicacid (1b) The parent molecule was prepared from 5-amino-8-hydroxy quinoline on reaction with diethyl ethoxymethelene malonate and cyclized in diethyl ether; further condensation with chloroethanol gave ester, which finally hydrolyzed to title compounds (Lee et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6-Chloro-1-(2-hydroxyethyl)-4-oxo-1,4-dihydro- [1,7]phenanthroline-3-carboxylicacid (1a) The parent molecule was prepared from 5-amino-8-chloro quinoline on reaction with diethyl ethoxymethelene malonate and cyclized in diethyl ether; further condensation with chloroethanol gave ester, which finally hydrolyzed to title compounds (Lee et al, 1992). 1 6-Hydroxy-1-(2-hydroxyethyl)-4-oxo-1,4-dihydro- [1,7]phenanthroline-3-carboxylicacid (1b) The parent molecule was prepared from 5-amino-8-hydroxy quinoline on reaction with diethyl ethoxymethelene malonate and cyclized in diethyl ether; further condensation with chloroethanol gave ester, which finally hydrolyzed to title compounds (Lee et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…1 6-Hydroxy-1-(2-hydroxyethyl)-4-oxo-1,4-dihydro- [1,7]phenanthroline-3-carboxylicacid (1b) The parent molecule was prepared from 5-amino-8-hydroxy quinoline on reaction with diethyl ethoxymethelene malonate and cyclized in diethyl ether; further condensation with chloroethanol gave ester, which finally hydrolyzed to title compounds (Lee et al, 1992). 1 6-Chloro-1-(2-hydroxyethyl)-4-oxo-1,4-dihydro- [1,7]phenanthroline-3-carbonyl chloride (2a) The mixture of 6-chloro-1-(2-hydroxyethyl)-4-oxo-1, 4-dihydro- [1,7]phenanthroline-3-carboxylic acid (1a) (0.01 mol) and thionyl chloride (0.01 mol) was refluxed using chloroform as a solvent in water bath at 80°C for 5-6 h in anhydrous condition with the help of calcium chloride guard tube, until the HCl gas evolution ceased, and then solvent was removed by distillation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorinated pyridoquinolones have been synthesized by Lee and Chang (Lee et al, 1992) and their biological activity has been studied. We have concentrated on nonfluorinated pyridoquinolones, synthesized several compounds by incorporating various substituted urea, thiourea and piperazine compounds at C-3 position and studied their antimicrobial activities (Patel and Chauhan, 2005;Patel et al, 2010a;Patel et al, 2010b), and found that these compounds showed good antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%